1993
DOI: 10.1002/ptr.2650070403
|View full text |Cite
|
Sign up to set email alerts
|

Garlicin—fact or fiction? the antibiotic substance from garlic (Allium sativum L.)

Abstract: It was in the early pioneer days of the antibiotic era when 'garlicin', the antibiotic agent from garlic (Alliurn satiuum L.), appeared for the first time in the scientific literature and was described as a substance isolated from garlic cloves with convincing pharmacological and clinical evidence concerning its antibiotic properties. In this article evidence for and against garlicin as a chemical entity will be reviewed in order to clarify more fully the known antibiotic activity of garlic clove extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
2
5
0
1
Order By: Relevance
“…There is also a high content of non-volatile compounds with well-known medicinal and therapeutic properties, such as amides, nitrogen oxides, phenolic compounds, especially flavonoids, proteins, saponins and sapogenins [3,4,5], as well as antioxidants, minerals (especially P, K and Se) and vitamins (especially vitamin C and vitamins of B complex) [6]. According to Koch and Lawson [7], dry garlic bulbs mainly consist of water (62–68%) and carbohydrates (26–30%), while proteins are detected in relatively less amounts (1.5–2.1%). Moreover, protein contents of 4–6% are also very common in various cultivars, considering the high dry matter content of the bulbs, while ash content ranges between 0.6% and 1.0%, and energy content is around 140 kcal 100 g –1 f.w.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a high content of non-volatile compounds with well-known medicinal and therapeutic properties, such as amides, nitrogen oxides, phenolic compounds, especially flavonoids, proteins, saponins and sapogenins [3,4,5], as well as antioxidants, minerals (especially P, K and Se) and vitamins (especially vitamin C and vitamins of B complex) [6]. According to Koch and Lawson [7], dry garlic bulbs mainly consist of water (62–68%) and carbohydrates (26–30%), while proteins are detected in relatively less amounts (1.5–2.1%). Moreover, protein contents of 4–6% are also very common in various cultivars, considering the high dry matter content of the bulbs, while ash content ranges between 0.6% and 1.0%, and energy content is around 140 kcal 100 g –1 f.w.…”
Section: Introductionmentioning
confidence: 99%
“…It is active against a great number of bacteria, viruses, fungi, and many other parasites [16][17][18]. In low concentrations, it inhibits the growth of Staphylococcus, Streptococcus, Bacillus, Brucella, Vibrio and Candida species [7,19].…”
mentioning
confidence: 99%
“…This might be due to the genetic variability extent that existed among the tested genotypes and local cultivars in moisture content. Similarly [ 38 ], revealed that bulbs of dry garlic genotypes varied from 62% to 68% in water content.
Fig.
…”
Section: Resultsmentioning
confidence: 99%